2008
DOI: 10.1136/adc.2007.134866
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in children with renal disease

Abstract: A high proportion of renal patients were vitamin D deficient/insufficient, particularly children of South Asian origin. High PTH values in the setting of reduced GFR might be due to vitamin D deficiency and should lead to estimation of serum 25(OH)D concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…The prevalence of 25(OH)D deficiency in adults with CKD2-4 has been reported at 71-82% and is closely related to CKD stage (13). There are little data in children, but a prevalence of 39-83% has been reported in children with CKD, although stratification with CKD stage is not described (14)(15)(16)(17)(18). Most authorities consider 25(OH)D levels .75 nmol/L (11,36,37) as adequate, but the 25(OH)D level required for its noncalcemic effects or levels required for autocrine/paracrine effects are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of 25(OH)D deficiency in adults with CKD2-4 has been reported at 71-82% and is closely related to CKD stage (13). There are little data in children, but a prevalence of 39-83% has been reported in children with CKD, although stratification with CKD stage is not described (14)(15)(16)(17)(18). Most authorities consider 25(OH)D levels .75 nmol/L (11,36,37) as adequate, but the 25(OH)D level required for its noncalcemic effects or levels required for autocrine/paracrine effects are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…PTH levels in their cohort improved from 122 to 80 pmol/L after 3 months but with wide variations, and the 25(OH)D and 1,25(OH) 2 D levels achieved are not mentioned; also, there is no reference made to any CKD stage-specific responses or racial differences in outcome (16). Belostotsky et al (14) found that 83% of their patients with renal disease (CKD stage not specified) had 25(OH)D levels below 30 ng/ml (75 nmol/L). Twenty children were given a single large dose (100,000 IU for children 5-10 years of age and 150,000 IU for children over 10 years) (40) of ergocalciferol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of interest, skin creams even with sun protection factor (SPF) levels as low as 15 can block off 99% of UV-B light. Several studies have confirmed that ethnic groups living in northern countries are at greater risk as increased melanin pigmentation and cultural practices with dress code may limit sun exposure [64].…”
Section: The Pandemic Of Vitamin D Deficiencymentioning
confidence: 98%
“…Importantly, CKD patients not only display impaired levels of 1,25(OH) 2 D 3 : also low circulating 25(OH)D 3 levels, irrespective of disease progression, are frequently observed in these patients, which further contribute to low 1,25(OH) 2 D 3 levels [70][71][72][73]. Recent studies addressed this issue in pediatric CKD patients and found vitamin D insufficiency and deficiency to be highly prevalent among them [74][75][76][77]. The lack of 25 (OH)D 3 can rationally be explained in cases of proteinuria, where DBP-bound 25(OH)D 3 is lost, but decreased sunlight exposure and malnutrition due to chronic illness, dietary restrictions, and decreased UVB-mediated synthesis of vitamin D 3 in the skin of CKD patients compared with individuals with normal kidney function have been proposed to underlie this deficit as well.…”
Section: Immune Consequences Of Vitamin D Insufficiency: Clinical Impmentioning
confidence: 99%